High-resolution Porites coral trace element record of core PAN08-2 from the Pandora Reef - Juan Pablo D extquotesingleOlivo; Malcolm T McCulloch (PANGAEA, 2022)
Trace element (Sr/Ca, Ba/Ca and U/Ca) high-resolution (~weekly) records from Porites coral cores from the Great Barrier Reef.
In: D extquotesingleOlivo, JP; McCulloch, MT (2022): High-resolution coral Ba/Ca records from the Great Barrier Reef [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.944992